Screening fungi for use as biocatalysts in self-healing concrete with protocol simulating concrete environment - Ahsanul Kabir Sumon; Krutika Invally; Lu-Kwang Ju (AIMS Bioengineering)
This work addresses the problem of having no existent protocol that closely simulates the harsh concrete environment, namely, high pH (about 13) and temperature (up to above 50 °C during cement hydration), for selecting microorganisms to use in microbe-effected self-healing concrete (MESHC). This problem critically impedes the progress of MESHC development, which has tremendous significance because concrete cracking reduces service life while making new concrete consumes substantial energy and emits a large amount of CO2. The objective of this work was to develop an effective and innovative screening protocol that mimics not only the concrete-relevant pH and temperature but also the essential process/scenario of MESHC, that is, microbial spores remain dormant through the harsh conditions during concrete mixing and curing and germinate later at the less harsh condition (pH 9–11, ambient temperature) in concrete cracks. The protocol includes 4 steps with increasing complexity to reduce strains for time-consuming steps. The first 2 steps screen for strains capable of vegetative growth on agar and liquid media with initial pH ≥ 10. Step 3 evaluates the spore germinability in medium with pH gradually decreasing from 12. In Step 4, spores were subjected to both high pH (12, 12.9) and temperature (45, 55 °C) for 2 h before being stored in the high-pH medium at room temperature for up to 21 days. Spores were finally collected and resuspended in pH 9.5 medium to observe germinability. 18 alkalotolerant strains were screened. Scopulariopsis brevicaulis (S. brevicaulis) is identified as the best candidate. Results also indicate the importance of incorporating designs to locally lower pH near spores, at least slightly (from 12.9 to 12), and to limit temperature to below 53 °C. Survivability of S. brevicaulis spores in contact with mortar undergoing cement hydration was also monitored. The work identifies promising fungi and indicates critical directions for developing spore-protection technologies for MESHC.